2022
DOI: 10.1108/lht-10-2021-0354
|View full text |Cite
|
Sign up to set email alerts
|

A research on digital learning system based on multiplayer online animation game

Abstract: PurposeThis research explores the appropriateness of using a digital learning system based on a multiplayer online animated game in firefighting education and training. Use of the game improved learning was effective. It can increase learners' understanding of the taught content and their willingness to learn.Design/methodology/approachThe research applies digital learning based on a multiplayer online animated game coupled with 3D and virtual reality (VR) technology. To verify the effectiveness of this approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Readers may be interested in recent research on immersive and engagement experiences in AR (Dağ et al , 2023; Dalili Saleh et al , 2021; Li and Liu, 2023), VR and AR experiences in libraries (Greene and Groenendyk, 2021), mobile business simulation games (Chen et al ., 2023), the metaverse (Feng et al , 2022), game animation design (Wu and Tu, 2023; Zhang and Chang, 2023); and game-based learning with AR (Liu et al ., 2023; Yu et al , 2024a, b).…”
Section: Virtual Reality (Vr) Augmented Reality (Ar) and Education Gamesmentioning
confidence: 99%
“…Readers may be interested in recent research on immersive and engagement experiences in AR (Dağ et al , 2023; Dalili Saleh et al , 2021; Li and Liu, 2023), VR and AR experiences in libraries (Greene and Groenendyk, 2021), mobile business simulation games (Chen et al ., 2023), the metaverse (Feng et al , 2022), game animation design (Wu and Tu, 2023; Zhang and Chang, 2023); and game-based learning with AR (Liu et al ., 2023; Yu et al , 2024a, b).…”
Section: Virtual Reality (Vr) Augmented Reality (Ar) and Education Gamesmentioning
confidence: 99%
“…Finally, the statistical results of the questionnaires showed that learners who used MLAR scored higher on Likert scales measuring learning behavioral intention, cognitive usefulness, cognitive ease of use and environmental interactivity. Liu et al (2023) developed a digital learning system for a multiplayer online animated game coupled with 3D and VR technologies for firefighting education. The results show that it can increase learners' understanding of the content being taught and stimulate the willingness to learn.…”
Section: Virtual and Augmented Technologies For Educationmentioning
confidence: 99%
“…Students only need a mobile phone or computer tablet to complete assignments. Digital business simulation games have been extensively used in college courses, and their effectiveness in improving student participation and learning outcomes has been widely recognized (Anderson and Lawton, 2009;Huang et al, 2022;H€ oyng, 2022;Chen et al, 2022a;Liu et al, 2022c).…”
Section: Introductionmentioning
confidence: 99%